مدى تأثر أسعار الأسهم بالتحيزات العاطفية للمستثمرين: دراسة تحليلية في سوق العراق للاوراق المالية - محمد عبد الامير عطية; زينب هادي نعمة (PROSPECTIVE RESEARCHES, 2023)
Behavioral finance aims at providing realistic explanations for many unusual situations in the financial markets and stock prices, including distortions, phenomena and price bubbles that occur in the stock market, and it also looks for treatments to avoid them through the perspective of behavioral biases, both cognitive and emotional. Therefore, this study will attempt to show the extent to which share prices in the Iraq stock exchange are affected by the three emotional biases: the loss aversion bias, the overconfidence bias and the status quo bias. The study showed that investors in the Iraqi stocks suffer from prejodices in a large manner, and the stock prices have been significantly affected with these prejodices, and that dealings relations were strong and morally significant.